(3bQBf cQje eY JYdjb HGdaGQSjIs
(3ChdgG (B:s
(3jHOC HaGJMI GdcJGH hJaSjQgG s
(3BNQgG (B:s
(3jfJgi HShQI GdENdGU hJaSjQgG s
(3HBNQgG hbajI HGSe hdi RGOg ai (B26 (3TgQ QLH SfI (B1070 (3g`s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdcJH GdSeGhjIs